Consumer Behavior Analysis as a Form of Pre-market Survey for the Black Pule (Alstonia spectabilis) Antimalarial Tablet Prototype: Analisis Perilaku Konsumen Sebagai Bentuk Survei Pre-market Tablet Prototipe Antimalaria Pule Hitam (Alstonia spectabilis) - Taek, Maximus Markus; Ma'arif, Burhan; Maulina, Novia; Muslikh, Faisal Akhmal; Lalong, Paulus Risan Funan (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Malaria is a disease caused by the protozoan parasite Plasmodium with a high incidence of spread that is still found in remote tropical places, especially areas around gardens, swamps, forests, and mines such as eastern Indonesia. The commonly used antimalarial drug chloroquine has experienced resistance, encouraging researchers to look for effective alternative treatments. Formulation development of Standardized Herbal Medicine (OHT) from black pule was carried out as a potential new alternative treatment as an antimalarial. Objectives: The purpose of this study was to determine the level of liking and quality assessment or characteristics of the prototype of antimalarial OHT tablets. Methods: The method used in this research is descriptive quantitative which aims to describe 57 panelists' perspective on the product and to analyze product marketing. In this research method includes hedonic test and hedonic quality test which is a series of organoleptic tests and consumer acceptance tests by tasting and observing the product followed by filling out a form according to what is felt and observed. Results: The results obtained from this research, namely the preference test of the overall characteristics of the prototype of antimalarial black pule tablets (Alstonia spectabilis) showed a good sensory impression and characteristics. The positive results obtained from all aspects have illustrated that the panelists have considerable interest in the prototype sample and assess that the prototype tablets are suitable for dissemination to the public. Conclusions: Based on the research, it can be concluded that the prototype of black pule (Alstonia spectabilis) tablets tested through hedonic and hedonic quality tests produced overall good results, characterized by the tendency of panelists to choose "Like" in the hedonic test of sensory impressions and positive values in the hedonic quality test.